PENENTUAN KONDISI OPTIMUM SUHU DAN WAKTU KARBONISASI PADA PEMBUATAN ARANG DARI SEKAM PADI - Satriyani Siahaan, Melvha Hutapea, Rosdanelli Hasibuan (Jurnal Teknik Kimia USU, 2013)
Charcoal is a solid porous material containing 80 - 90 % of carbon being produced from combustion at high temperatures (carbonization ), that the material only carbonized and not oxidized become carbon dioxide. The research is aimed to know the optimum conditions on the process of carbonization from the rice husks. The carbonization process conducted in temperatures 400 oC, 500 oC, and 600 oC with variations in time 30 minutes, 60 minutes, 90 minutes and 120 minutes. Optimum conditions carbonization for rice husk at temperature 400 oC for 120 minutes with a carbon content 41,3 %, moisture content 6,1 %, ash content 32,6 % and volatile matter content 20,5 %. Keywords : charcoal, carbonization, rice husk